Mineralogical characterization of soils derived from effusive rocks from plateau in south Santa Catarina, Brazil - Teske, Rodrigo; Almeida, Jaime Antonio; Hoffer, Andrey; Lunardi Neto, Antonio (Revista de Ciências Agroveterinárias, 2013)
The simultaneous presence of gibbsite, kaolinite, 2:1 clay minerals with Al-hydroxy polymers and interstratified minerals in acid soils and desaturated in southern Brazil can be seen as contradictory, but not rare. How correct identification of these clay minerals is difficult to perform, the evolution of these soils may simply end up being attributed to a range of moderate weathering. To better understand the genesis of soils in southern highlands of Santa Catarina, studies were conducted of mineralogical clay rocks and their array of seven soil profiles along two topossequences. The mineralogical analyzes were performed by X-ray diffractometry (XRD) using the usual pretreatment and a pretreatment with hot (250°C) 3.5 mol L-1 solution. The levels of oxides of Si, Al and Fe were determined after dissolving the samples in sulfuric acid. The rocks show similar mineralogy, except in amounts of plagioclase, pyroxene and quartz. All soils had low crystallinity of kaolinite and traces of 2:1 clay minerals in the form of interstratifi ed and/or 2:1 clay minerals with Al-hydroxy polymers, that/which remained in the soil due to intercalation of the polymers of Al and/or Fe in interlayers. The diminutive proportions of gibbsite are due to the complex effect of soil organic matter (SOM) on the crystallization of Al hydroxides and also due to the leaching environment was not sufficiently severe as to dominate the processes of alitization. In Kandiudox the main process of changing the source material was monossialitization while Haplumbrept showed hydrolysis process tending to alitization.